Spatial Distribution of Root and Crown Rot Fungi Associated With Winter Wheat in the North China Plain and Its Relationship With Climate Variables - Xu, Fei; Yang, Gongqiang; Wang, Junmei; Song, Yuli; Liu, Lulu; Zhao, Kai; Li, Yahong; Han, Zihang (Frontiers in Microbiology, 2018)
The distribution frequency of pathogenic fungi associated with root and crown rot of winter wheat (Triticum aestivum) from 104 fields in the North China Plain was determined during the period from 2013 to 2016. The four most important species identified were Bipolaris sorokiniana (24.0% from roots; 33.7% from stems), Fusarium pseudograminearum (14.9% from roots; 27.8% from stems), Rhizoctonia cerealis (1.7% from roots; 4.4% from stems), and Gaeumannomyces graminis var. tritici (9.8% from roots; 4.4% from stems). We observed that the recovered species varied with the agronomic zone. Fusarium pseudograminearum was predominant in regions 1 and 3, whereas F. graminearum, F. acuminatum, and R. cerealis were predominant in regions 2 and 4. The incidence of F. pseudograminearum and R. cerealis were significantly different between regions 1 and 4, while no significant association was found in the proportion of the other species and the agronomic zones. A negative correlation between the frequency of occurrence of F. pseudograminearum and mean annual precipitation during 2013–2016 (r = -0.71; P < 0.01) in the North China Plain and a positive correlation between the mean annual precipitation during 2013–2016 and the frequency of occurrence of F. asiaticum (r = 0.74; P < 0.01) was observed. Several Fusarium species were also found with low frequencies of ~2.1%–3.4 % (F. graminearum, F. acuminatum, and F. sinensis) and ~0.1%–1.3% (F. equiseti, F. oxysporum, F. proliferatum, F. culmorum, F. avenaceum, and F. asiaticum). In more than 93% of the fields, two or more root and crown rot species were isolated from the root and crown tissues of wheat. The coexistence of Fusarium spp. and B. sorokiniana in one field (65.4%) or in individual plants (11.6%) was more common than for the other species combinations. Moreover, this is the first report on the association between F. sinensis and root and crown rot of wheat. Our results would be useful in the framing guidelines for the management of root and crown rot fungi in wheat in different agronomic zones of the North China Plain.